To fill in the blanks, we have:
- The expression \( 8^{(3)} - _ - _ \) can be written as \( 8^{(3)} = (8)(8)(8) \).
- Therefore, the two blanks can be filled with the same thing, which is \( 8^{(3)} \).
So, we have:
- First blank: \( 8^{(3)} \)
- Second blank: \( 8^{(3)} \)
- Final evaluation: \( 8^{(3)} = (8)(8)(8) = 512 \)
Putting it all together:
\[ 8^{(3)} - 8^{(3)} - 8^{(3)} \]
Thus, the filled-in version looks like this:
\[ 8^{(3)} - 8^{(3)} - 8^{(3)} \]
And,
\[ 8^{(3)} = (8)(8)(8) = 512 \]